1998
DOI: 10.1111/j.1571-9979.1998.tb00170.x
|View full text |Cite
|
Sign up to set email alerts
|

Between Vengeance and Forgiveness: South Africa's Truth and Reconciliation Commission

Abstract: Citizens of South Africa are confronting a painful past through the new nation's Truth and Reconciliation Commission, or TRC, which thus far has heard thousands of reports (many televised) about murders, torture, and other human rights abuses that took place during the apartheid era. South Africa's TRC is grounded in a constitutional commitment to the African concept of “ubuntu,” or humaneness. Amnesty is available on a conditional basis to alleged perpetrators. The author assesses the potential restorative po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 4 publications
1
65
0
1
Order By: Relevance
“…According to the predictions of some researchers (Minow 1998; Zarzycka 2016), forgiveness should be seen as a psychological-spiritual process, which has a complex structure and is conditioned by many factors of personal and social nature, as well as religious nature; hence, we can talk about different types of forgiveness, which confirmed previous (Zarzycka 2016) as well as current research. It should be added that forgiveness, and its special component regarding the sense of forgiveness by God, is an important component of man’s religiousness.…”
Section: Discussion Of the Results And Conclusionsupporting
confidence: 87%
“…According to the predictions of some researchers (Minow 1998; Zarzycka 2016), forgiveness should be seen as a psychological-spiritual process, which has a complex structure and is conditioned by many factors of personal and social nature, as well as religious nature; hence, we can talk about different types of forgiveness, which confirmed previous (Zarzycka 2016) as well as current research. It should be added that forgiveness, and its special component regarding the sense of forgiveness by God, is an important component of man’s religiousness.…”
Section: Discussion Of the Results And Conclusionsupporting
confidence: 87%
“…Although positive expectations from the hearings were generally high among victims, offenders, and others (e.g., observers), questions were raised about the net benefits, how widespread benefits were, and the extent of harm experienced by victims. Exploring the roles of witnesses, perpetrators, and bystanders in TRC hearings, Minow (1998) suggested that the TRC facilitated resolution of pain, but criticisms have been advanced (Chapman & Spong, 2003). Some suggested the methodological process employed by the TRC became perpetrator focused by reducing victims’ testimonials to basic quantitative codes (Statman, 2000), whereas others asserted the victims did not receive appropriate compensation for their suffering (Gibson, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Emotions of victims and defendants are elicited and expressed during and as part of procedures, including sadness, anger, and hatred on the part of victims, and shame, guilt, and remorse among the perpetrators (Gobodo-Madikizela, 2002). The emotions of judges, lawyers, and audiences present at these procedures (e.g., postwar Belgium; Elster, 2004, p. 216), and of “sympathetic witnesses” and “listeners” (Minow, 1998) add to the emotional dynamics of transitional justice procedures. Forgiveness as an “emotional practice” (Jeffery, 2008, p. 180) is part of contemporary TJ procedures, in criminal trials as well as in TRCs.…”
Section: Great Expectations: Emotions and Transitional Justicementioning
confidence: 99%
“…Rather emotions have become an essential justification for its aims, objectives, and ultimately achievements. TJ has adopted a language of emotional healing rather than the language of justice, as Minow (1998, p. 327) observed early on. In this vein, truth telling, accountability, and justice (Doak, 2011) are seen as mechanisms whose foremost role is to lead to emotional recovery and healing of individual victims.…”
Section: Great Expectations: Emotions and Transitional Justicementioning
confidence: 99%